Transformative Leadership from Marginalized Origins: A Model for Community Empowerment and Socio-Economic Change - Fikri Fadilah; Beni Ahmad Saebani; Ridwan Eko Prasetyo (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the transformative leadership model implemented by a village head with a background as a former thug and its implications for the community empowerment process in Cikuya Village, Cicalengka District, Bandung Regency, Indonesia. Village leaders with non-conventional backgrounds are often perceived negatively and considered problematic in the context of village governance. However, in practice, such figures have the potential to bring about significant social change, particularly in village development and strengthening community participation. This study uses a qualitative approach with juridical-sociological methods to deeply understand the socio-political dynamics, leadership patterns, and the legitimacy of the village head's power from the perspective of constitutional law and Islamic values. Data collection techniques included in-depth interviews, participatory observation, and documentation, involving the village head, village government officials, community leaders, and residents of Cikuya Village as key informants. Data analysis was carried out using the siyasah dusturiyah theoretical framework as proposed by Ibn Taymiyyah, which emphasized that the legitimacy of leadership is not determined by a person's social background, but rather by the leader's capacity to carry out mandates, uphold justice, and create benefits for the wider community. Through this approach, research is expected to be able to reveal the process of social transformation from a thug figure to a formal leader who is recognized legally and socially. Apart from that, this research is also expected to show how leadership can form effective, responsive, and inclusive patterns, as well as to provide theoretical contributions to the study of village leadership and practical contributions to strengthening village governance.